Explaining the pattern of childbearing behaviors in couples: Protocol for a focused ethnographic study - Faranak Safdari-Dehcheshmeh; Mahnaz Noroozi; Fariba Taleghani; Soraya Memar (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: One of the most basic life events is fertility or reproduction, which, although known as a social phenomenon, is a complex and multidimensional concept with economic, cultural, political, and religious significance. The present study aims to explain the pattern of childbearing behaviors in couples. MATERIALS AND METHODS: This study is a focused ethnographic qualitative research. Participants of this study will be 20-35 years old couples who, using purposeful sampling method, will be selected from comprehensive health centers, ultrasound centers, laboratories, premarital counseling centers, offices of obstetricians and midwives, universities, shopping centers, cinemas, parks, restaurants, and entertainment centers in Isfahan, Iran. Sampling will continue considering the strategy of maximum variation in terms of age, occupation, education, and economic status until data saturation is reached. Data will be collected through semi-structured and in-depth individual interviews, focus group discussions, observation, field notes, daily notes, and document analysis. Simultaneous with data collection, the data will be analyzed using the thematic analysis method based on Braun and Clarke's approach. CONCLUSION: This present study is expected to lead to a deep understanding and identification of the attitudes, beliefs, and values of couples with regard to childbearing. Moreover, by understanding the pattern of childbearing behaviors of couples, useful information will be provided to the policymakers and planners for effective planning in the field of healthy childbearing. The findings can also be used in reproductive health counseling for newly married couples and community-based interventions.